(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
HIV/AIDS has been mayhem for the society across theworld. It has wrecked the lives of many and is an epidemic which has thepotential to ruin the entire generation. It is very difficult to measure theextent and the amount of destruction that HIV/AIDS can lead to. HIV/AIDS is amedical as well as socio-economic issue. India is not an exception; AIDS hasinfiltrated the Indian society from lowest to the highest strata of population.HIV/AIDS not only adversely impacts the physical health of the infected butalso affects his or her economic status. HIV/AIDS can lead to a state ofeconomic deprivation and thus forcing people to die. Women are the worstaffected by this epidemic. Karnataka is one of the major states out of 6 highHIV prevalent sates of India. This paper aims to study the economic impact ofHIV/AIDS on women existing with HIV/AIDS in Karnataka, India.